Towards a Pattern Language Approach to Document Description - Robert Waller; Judy Delin; Martin Thomas (Discours)
Pattern libraries, originating in architecture, are a common way to share design solutions in interaction design and software engineering. Our aim in this paper is to consider patterns as a way of describing commonly-occurring document design solutions to particular problems, from two points of view. First, we are interested in their use as exemplars for designers to follow, and second, we suggest them as a means of understanding linguistic and graphical data for their organization into corpora that will facilitate descriptive work. We discuss the use of patterns across a range of disciplines before suggesting the need to place patterns in the context of genres, with each potentially belonging to a “home genre” in which it originates and to which it makes an implicit intertextual reference intended to produce a particular reader response in the form of a reading strategy or interpretative stance. We consider some conceptual and technical issues involved in the descriptive study of patterns in naturally-occurring documents, including the challenges involved in building a document corpus.